Student’s Learning Motivation In Implementing Differentation Learning In Pancasila Education - Isna Nur Hudatul Hasanah; Mukhamad Murdiono (PT Publikasiku Academic Solution, 2024)
This study aims to evaluate the level of students' learning motivation in the application of product differentiation learning strategies in Pancasila Education subjects. This study uses a quantitative descriptive method, with data collection through questionnaires. The questionnaires were distributed to two classes, totaling 67 students of grade VIII at SMP Negeri 15 Yogyakarta, with random class selection. The questionnaire includes five indicators of student learning motivation, namely enjoyment in learning, willingness to work, desire to get high grades, awareness to learn, and independence. The results showed that the average of all indicators of student learning motivation reached 83.9%, which is a very high category. This indicates that the application of product differentiation learning strategies to the material of national spirit and commitment in Pancasila Education subjects can significantly increase student learning motivation.